A novel flow cytometry-based platelet aggregation assay - De Cuyper, Iris M; Meinders, Marjolein; van de Vijver, Edith; de Korte, Dirk; Porcelijn, Leendert; de Haas, Masja; Eble, Johannes A; Seeger, Karl; Rutella, Sergio; Pagliara, Daria; Kuijpers, Taco W; Verhoeven, Arthur J; et al. (Blood, 2013)
The main function of platelets is to maintain normal hemostasis. Inefficient platelet production and/or defective platelet function results in bleeding disorders resulting from a wide range of genetic traits and acquired pathologies. Several platelet function tests have been developed for use in the clinic and in experimental animal models. In particular, platelet aggregation is routinely measured in an aggregometer, which requires normal platelet counts and significant blood sample volumes. For this reason, the analysis of thrombocytopenic patients, infants, and animal models is problematic. We have developed a novel flow cytometry test of platelet aggregation, in which 10- to 25-fold lower platelet counts or sample volumes can be used, either of platelet-rich plasma or whole blood from human subjects or mice. This setup can be applied to test in small assay volumes the influence of a variety of stimuli, drugs, and plasma factors, such as antibodies, on platelet aggregation. The presented principle stands as a novel promising tool, which allows analysis of platelet aggregation in thrombocytopenic patients or infants, and facilitates studies in platelets obtained from experimental animal models without the need of special devices but a flow cytometer.